MCDM Approach for Evaluating Salespeople in Traditional Markets: A Case Study in an Indonesian Grocery Store - Gilang Prasetyo, Wahyu; Kurniawan, V. Reza Bayu; Kusmendar, Kusmendar; Rahmawati, Titik; Yulia Sari, Eka; Priyanto, Agung (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
In the current business activities characterized by technological integration, the role of salespeople remains crucial as the frontline in enhancing product sales. Due to their contribution, it is imperative for companies to evaluate their performance. This research proposes an evaluation model for salespersons using a multiple-criteria decision-making (MCDM) approach. Two MCDM methods, namely fuzzy AHP and EDAS, are employed to determine the weight of evaluation criteria and rank 13 salespersons in a grocery store situated in an Indonesian traditional market. This study considers seven criteria: revenue (C1), honesty (C2), communication skills (C3), empathy (C4), extensive relationships (C5), work motivation (C6), and responsibility and discipline (C7). Using fuzzy AHP, criteria C2, C6, and C3 are identified as the main priority. Subsequently, the criteria weights are integrated into the EDAS calculation to rank the 13 salespersons. Salesmen SP2, SP3, and SP6 emerge as the top performers. This research provides an applicable evaluation model for decision-makers in the store, enabling them to assess their salespeople not solely based on quantitative output but also considering other criteria that may have a lasting impact. Keywords: EDAS, evaluation performance, fuzzy AHP, salespeople